Identifying and Creating Sources of Competitive Advantage in an Enterprise’s Value Chain - Walas-Trębacz, Jolanta (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
The article emphasises that an enterprise’s management can identify sources of competitive advantage in the market to help it effectively shape its value chain structure. In order to identify these sources and focus on the relevant processes that create value added for the customer and other stakeholders, management should evaluate the effectiveness of the existing value chain. To that end, an important task is to identify the most valuable sources contributing to competitive advantage in the existing value chain. To configure an enterprise’s value chain so that it reaches the highest added value, management should take into account, in choosing a model and structure, concepts that are subject to numerous changes over time. The article focuses mainly on presenting the classification and review of selected concepts that allow management to set the directions it will follow to improve the enterprise value chain, primarily from the point of view of the capabilities needed to effectively develop and maintain key sources of competitive advantage. In addition, one group of concepts included in a classification – resource-based competitive advantages – is presented in greater detail. At present, they are still an important inspiration for business managers in improving the structure of the value chain.